The influence of the manuscript on postmodern literature The modern Iraqi narrative model (Journal of the College of Basic Education, 2022)
The employment of the manuscript in the literary narrative is a change that deserves to be monitored, especially in recent decades. A number of critics tracked it within the studies of postmodern literature, because of the milestone it created in the Iraqi narrative experience, the data of which cannot be overlooked critically and creatively. There have emerged literary works that succeeded in successfully expressing the ranges of its wide applications, technology and idea, in a manner consistent with the data of the human experience, and came very close to social reality and did not fly far from it, while other works came below the level of ambition due to the lack of creative talent, and the failure to comprehend the strips of employing technology. .